Prekmurski členki v Pleteršnikovem slovarju - Agrež, Maruška (Slavia Centralis, 2020)
PREKMURIAN PARTICLES IN PLETERŠNIK’S DICTIONARYThis paper discusses Prekmurian particles in Pleteršnik’s dictionary and other relevant word inventories and selected texts written in the Prekmurian standard language. The particle, typical of the Prekmurian language is ešče. Some particles are specifc to Eastern Slovene while others also occur in Kajkavian. Prekmurian particles differ from Central and Standard Slovene particles in a lexical, phonological, and derivational sense. Many Prekmurian particles are etimologically similar to their Proto-Slavic variants.
Keywords: Pleteršnik’s dictionary; particles; the Prekmurian language; the Prekmurian standard language; Eastern Slovene; the Kajkavian language